2003
DOI: 10.1002/macp.200390091
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Copolymers of Ethylene and Diolefins Containing Pendent Functional Groups

Abstract: The catalyst [Me2C(Flu)(3‐MeCp)ZrCl2] (1), activated by MAO, was used for the copolymerization of ethylene and 1,7‐octadiene (OD) to form copolymers with pendent double bonds. The properties of the copolymers were strongly dependent on the purity of the comonomer. Formation of ethylene‐rich sequences and increased levels of crosslinking were observed with highly purified 1,7‐octadiene. Catalysts 1 and [Me2Si(Flu)2ZrCl2] (2), activated by MAO, were used for the copolymerization of ethylene and 7‐methyl‐1,6‐octa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Nevertheless, it has been shown that these properties can be improved by introducing long-chain branching (LCB) to linear polyolefins [2][3][4]. Different methodologies have been developed, such as the ethylene copolymerization with vinylterminated polyolefins (macromonomers) [5,6], copolymerization with a non-conjugated α,ωdiene [7][8][9][10][11], as well as processes involving radical mechanisms [12][13][14][15][16][17][18]. Nevertheless, the materials produced with these methodologies generally exhibit complex molecular structures and/or uneven branch distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been shown that these properties can be improved by introducing long-chain branching (LCB) to linear polyolefins [2][3][4]. Different methodologies have been developed, such as the ethylene copolymerization with vinylterminated polyolefins (macromonomers) [5,6], copolymerization with a non-conjugated α,ωdiene [7][8][9][10][11], as well as processes involving radical mechanisms [12][13][14][15][16][17][18]. Nevertheless, the materials produced with these methodologies generally exhibit complex molecular structures and/or uneven branch distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, because of the radical mechanisms involved in these treatments, ample control over LCB formation is rather impossible; hence, polymers with complex structures are obtained in those cases. In-reactor technologies such as copolymerization of ethylene with either in situ-formed or previously isolated macromonomers, , or with a nonconjugated α,ω-diene have also been developed. Nevertheless, only a limited number of catalyst systems have been shown to efficiently generate and incorporate macromonomers, while the second approach is limited by the rather scarce availability of α,ω-dienes and by the uneven distribution of LCB in the final polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the previous in situ methods, this method suits most catalyst systems and appears to be more efficient and commercially feasible for the production of LCBed polypropylenes. Some systematic investigations have been carried out for ethylene copolymerization with nonconjugated α,ω-dienes for LCBed polyethylenes. However, although there are some reports in the literature about the copolymerization of propylene with nonconjugated dienes, few detailed fundamental studies have been conducted for the copolymerization and evaluation of the effects of LCB on rheological properties. In this article, we report a systematic study on the copolymerization of propylene with 1,9-decadiene and 1,7-octadiene with rac -Me 2 Si(2-MeBenz[ e ]Ind) 2 ZrCl 2 (MBI)/MMAO catalyst system, and the characterization of microstructure and rheological properties of the obtained LCBed PP samples.…”
Section: Introductionmentioning
confidence: 99%